Limitations in Simplified Approach in Assessing Performance of Façade under Blast Pressures - Lumantarna, R.; Ngo, T.; Mendis, P. (Civil Engineering Dimension, 2012)
The main function of building facades, which often consists of glazing windows, is to provide protection to the occupants and contents of the building from external hazards. In a blast event, the facade component of a building may become the weakest link of the structure, whereby its breach may lead to blast pressure ingress and hazardous projectiles into a structure. This paper reports part of a study to establish the performance of glass windows under blast pressures. Two modelling techniques were used to simulate the response of a façade panel. They are the Single Degree of Freedom (SDOF) modelling technique and the Finite Element (FE) modelling technique. Although the SDOF approach can be used with a reasonable degree of accuracy, the limitations of its basic assumption lead to loss of details in the idealisation process. This paper presents an attempt to establish performance indices of a façade panel, and to identify the discrepancies between simplified approach and the detailed numerical modelling approach analysis.